Poverty Reduction Strategies in Action: Perspectives and Lessons from Ghana - Amoako-tuffour; Armah (Lexington Books, 2007)
Since the inception of the HIPC Initiative, the story of the design and implementation of poverty alleviation strategies has largely been told through the filters of development partners and the Bretton Woods Institutions. Poverty Reduction Strategies in Action examines the efforts in Ghana to reduce poverty and initiate changes that it believes are essential to ensure a prosperous future for its citizens in the 21st century. It chronicles the achievements, pitfalls, and looming challenges of a government, its people, and its external partners in fashioning out and implementing anti-poverty and pro-growth policies. This edited volume, by a group of independent researchers, examines Ghana's experience: what was done, how it was done, what was left undone, the lessons learned, and fills the void in the development literature.